The Electronic Community Park Audit Tool (eCPAT): Exploring the Use of Mobile Technology for Youth Empowerment and Advocacy for Healthy Community Policy, Systems, and Environmental Change - Besenyi, Gina M.; Schooley, Benjamin; Turner-McGrievy, Gabrielle M.; Wilcox, Sara; Wilhelm Stanis, Sonja A.; Kaczynski, Andrew T. (Frontiers in Public Health, 2018)
Empowering and engaging youth in advocacy and participatory action research (PAR) for healthy community environments is an emerging approach to reducing the childhood obesity epidemic. Technology is a promising strategy for engaging youth in such efforts. The Community Park Audit Tool (CPAT) is user-friendly tool for evaluating the ability of parks to promote youth physical activity. Recently an electronic version of the tool (eCPAT) was developed and validated. The purpose of this study was to explore the use of eCPAT mobile technology on youth empowerment and advocacy. This study examined tool usability, youths' technology access, use, and readiness for PAR efforts, effectiveness of mobile technology on youth empowerment and advocacy, interaction effects between tool format and regular technology use, and tool format preferences. Youth ages 11–18 years were recruited and randomized into one of three study conditions: Control (no audit), paper (CPAT), and mobile technology (eCPAT). Intervention youth completed two park audits using assigned format. A subsample of youth in the Control group completed both CPAT and eCPAT audits for comparison. Independent samples t-tests and MANCOVAs explored differences in post-project levels of tool usability and empowerment and advocacy scores between groups. Multivariate linear regression analysis explored the interaction between Control, Paper, or eCPAT group membership and mean technology use in predicting empowerment and advocacy. Youth (n = 124) completed pre and post surveys. The majority of youth had access to technology (smartphone 77.4%, tablet/iPad 67.7%). Youth used mobile technology at least once a day to use apps (M = 7.8, SD = 3.2), browse the web (M = 6.3, SD = 3.3), and search for information (M = 6.3, SD = 3.5). Youth were also ready and willing to use technology for PAR (M = 3.42–3.59). No main or interaction effects were found for post-project levels of youth empowerment or advocacy. However, the eCPAT tool had high usability scores, was better liked, and was preferred by youth over paper-pencil methods. Mobile technologies are ubiquitous and a preferred strategy among youth for engagement in community change. Future studies should explore mobile technology as a potential strategy for engaging youth in ongoing PAR efforts to achieve successful engagement and advocacy in community healthy environmental change.